CD45 Phosphatase Inhibits STAT3 Transcription Factor Activity in Myeloid Cells and Promotes Tumor-Associated Macrophage Differentiation - Kumar, Vinit; Cheng, Pingyan; Condamine, Thomas; Mony, Sridevi; Languino, Lucia R; McCaffrey, Judith C; Hockstein, Neil; Guarino, Michael; Masters, Gregory; Penman, Emily; Denstman, Fred; Xu, Xiaowei; et al. (Immunity (Cambridge, Mass.), 2016)
Recruitment of monocytic myeloid-derived suppressor cells (MDSCs) and differentiation of tumor-associated macrophages (TAMs) are the major factors contributing to tumor progression and metastasis. We demonstrated that differentiation of TAMs in tumor site from monocytic precursors was controlled by downregulation of the activity of the transcription factor STAT3. Decreased STAT3 activity was caused by hypoxia and affected all myeloid cells but was not observed in tumor cells. Upregulation of CD45 tyrosine phosphatase activity in MDSCs exposed to hypoxia in tumor site was responsible for downregulation of STAT3. This effect was mediated by the disruption of CD45 protein dimerization regulated by sialic acid. Thus, STAT3 has a unique function in the tumor environment in controlling the differentiation of MDSC into TAM, and its regulatory pathway could be a potential target for therapy.